The Synthesis, Properties, and Stability of Lithium-Containing Nanostructured Nickel-Doped Ceramics - Artem L. Kozlovskiy; Maxim V. Zdorovets; Ainagul A. Khametova; Dmitriy I. Shlimas (Gels, 2022)
Lithium-containing ceramics have several great potential uses for tritium production, as well as its accumulation. However, their use is limited due to their poor resistance to external influences, mechanical pressure, and temperature changes. In this work, initial nanostructured ceramic powders were obtained using the sol-gel method, by mixing TiO2 and LiClO4·3H2O with the subsequent addition of NiO nanoparticles to the reaction mixture; these powders were subsequently subjected to thermal annealing at a temperature of 1000 °C for 10 h. Thermal annealing was used to initiate the phase transformation processes, and to remove structural distortions resulting from synthesis. During the study, it was found that the addition of NiO nanoparticles leads to the formation of solid solutions by a type of Li0.94Ni1.04Ti2.67O7 substitution, which leads to an increase in the crystallinity and structural ordering degree. At the same time, the grain sizes of the synthesized ceramics change their shape from rhomboid to spherical. During analysis of the strength characteristics, it was found that the formation of Li0.94Ni1.04Ti2.67O7 in the structure leads to an increase in hardness and crack resistance; this change is associated with dislocation. When analyzing changes in resistance to cracking, it was found that, during the formation of the Li0.94Ni1.04Ti2.67O7 phase in the structure and the subsequent displacement of the Li2TiO3 phase from the composition, the crack resistance increases by 15% and 37%, respectively, which indicates an increase in the resistance of ceramics to cracking and the formation of microcracks under external influences. This hardening and the reinforcing effect are associated with the replacement of lithium ions by nickel ions in the crystal lattice structure.